Aeromagnetic Anomalies in Central Yarlung‐Zangbo Suture Zone (Southern Tibet) and Their Geological Origins. Issue 2 (1st March 2020) - Wang, Jie; Yao, Changli; Li, Zelin
Abstract: Two subparallel east‐west trending linear aeromagnetic anomalies are observed along the central Yarlung‐Zangbo suture zone in southern Tibet. The Yarlung‐Zangbo suture zone represents the boundary of the Eurasian and Indian plates and records the subduction of the Neo‐Tethyan oceanic slab and subsequent continental collision. The two magnetic lineaments are spatially associated with the Gangdese batholith and Xigaze ophiolites, which are separated by the Xigaze fore‐arc basin that is filled with nonmagnetic sedimentary sequences. The Mesozoic‐Cenozoic Gangdese batholith is characterized by widespread I‐type granitoids. The Xigaze ophiolites are dominated by serpentinized mantle peridotites. To investigate the geological origins and deep structures of the magnetic sources of the two magnetic lineaments, a 3‐D inversion of aeromagnetic anomaly data was undertaken. By analyzing our inversion model and further magnetic modeling, it is proposed that the Gangdese batholith has a magmatic root with higher magnetization than the exposed granitoids, indicating that the deeper part of the Gangdese batholith may contain more mafic constituents than the shallow part. The subsurface part of the Xigaze ophiolites resembles a thin slab dipping to the south, implying that the deep‐seated Xigaze ophiolites are also serpentinized and retain complete structure. Key Points: The 3‐D inversion and magnetic modeling were used to study the two east‐west parallel magnetic lineaments in the central Yarlung‐Zangbo suture zone The north magnetic lineament is caused by the Gangdese granitoid batholith with a strongly magnetized mafic magmatic root The south magnetic lineament is caused by the Xigaze ophiolites, of which the deep parts are also serpentinized and complete